Spontaneous Intestinal Perforation and Necrotizing Enterocolitis: A 16-Year Retrospective Study from a Single Center - Suply, Etienne; Leclair, Marc-David; Neunlist, Michel; Roze, Jean-Christophe; Flamant, Cyril (European Journal of Pediatric Surgery, 2015)
Background Necrotizing enterocolitis (NEC) and spontaneous intestinal perforation (SIP) are serious abdominal conditions that affect preterm infants but are poorly understood. This single-center retrospective study was performed to identify the factors associated with NEC and SIP.Methods This study involved 3,464 preterm infants recruited over 16 years. A total of 136 NEC and 24 SIP were analyzed and adjusted odds ratios (aOR) were determined by logistic regression.Results Compared with the controls, NEC was associated with a Z-score for birth weight lower than –1 (aOR = 2.1 [1.1–3.9], p = 0.02) and lower than –2 (aOR = 4.4 [1.8–10.4], p < 0.01). NEC was associated with gestational ages of less than 31 weeks and with breech presentations (aOR = 1.5 [1.0–2.3], p = 0.03). In contrast, compared with the controls, SIP was associated with gestational ages of less than 26 weeks (aOR = 17.4 [3.1–96.2], p < 0.001) and multiple pregnancy (aOR = 2.9 [1.2–6.9], p = 0.02). Rates of mortality and cerebral lesions were higher in patients with NEC (25.0 and 13.2%, respectively) than with the controls (10.1 and 6.9%, respectively) and similar between patients with SIP (12.5 and 8.3%, respectively) and the controls.Conclusion NEC and SIP differed in risk factors and prognosis. Early distinction of SIP from NEC could impact on surgical decision.
Keywords: necrotizing enterocolitis; spontaneous intestinal perforation; risk factors; very low-birth-weight infants